2019
DOI: 10.1016/j.algal.2019.101430
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor pilot trial integrating a sidestream microalgae process for the treatment of centrate under non optimal climate conditions

Abstract: This study was carried out to assess the efficiency of a pilot-scale bubble-column reactor to remove nitrogen in centrate from the biosolid dewatering of a municipal wastewater treatment plant whilst producing biomass for agricultural purposes. The column was inoculated with a mixed community of Scenedesmus and Chlorella spp. and operated outdoor in batch for 55 days and in continuous for further 130 days. In continuous, the average daily biomass productivity was 40 ± 62 mg TSS L −1 d −1 and the average NH 4 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…To avoid serious pollution problems, wastewater effluents must be properly treated prior to their discharge into natural water bodies (Song et al, 2018). Although urban wastewater treatment plants (WWTPs) are now extremely efficient as regards removing pollutants, they consume huge amounts of energy (Ling et al, 2019;Marazzi et al, 2019) and the nutrients are usually lost by nitrogen stripping or phosphorus precipitation (Whitton et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid serious pollution problems, wastewater effluents must be properly treated prior to their discharge into natural water bodies (Song et al, 2018). Although urban wastewater treatment plants (WWTPs) are now extremely efficient as regards removing pollutants, they consume huge amounts of energy (Ling et al, 2019;Marazzi et al, 2019) and the nutrients are usually lost by nitrogen stripping or phosphorus precipitation (Whitton et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from ambient conditions (mainly solar light and temperature), there are many other factors that influence microalgae growth: PBR design, mixing rate, nutrient loading rates, microalgae strains, biomass and hydraulic retention time (BRT, HRT), competition with other microorganisms, inhibition by toxic substances, etc. (Cho et al, 2019;Marazzi et al, 2019). Some of these factors have been independently evaluated in outdoor flat-panel MPBRs in previous studies ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Reject liquid from sludge treatment (sidestream) in a typical municipal WWTP has 7 to 12 times higher N and P concertation as compared to the mainstream and therefore, is the first target for NR due to smaller volume and Sustainability 2019, 11, 3435 3 of 12 better recovery rates. However, different N and P concentrations have been stated in other studies, too [10,11].…”
Section: Nutrient Recovery Routes From Sewage Sludgementioning
confidence: 80%
“…More than 15 full-scale units mainly producing struvite Pearl, Multiform, Airprex see [10] Lack of economic drivers and regulations for nutrient recovery [10] Europe Germany (10), Netherlands (10), Belgium (6), France (2), Spain (2), Italy (1), UK (2), Denmark (4) Variety of technologies including Airprex, Anphos, Elophos see [10] Mainly producing struvite from both municipal and industrial wastewater It can be concluded that the low market price for fertilizers from phosphate rocks challenge the economic viability of nutrient recovery technologies, especially when the candidate technology does not provide additional operational benefits or a directly marketable product. The integration potential of a technology or a recovered material into existing infrastructure increases the chance to be in the successful class technologies.…”
Section: North Americamentioning
confidence: 99%
“…Microalgae/bacteria consortia have been recently suggested as effective in the treatment of different kinds of urban [15][16][17][18], as well as agro-industrial [19], wastewater. According to some authors, microalgae-based processes are not suitable to treat dairy wastewater as such, due to the high polluting load they carry [20,21].…”
Section: Introductionmentioning
confidence: 99%